Železo in sanje - Koršič, Igor (Slavistična revija, 2017)
According to an influential tradition of film theory, the mediality of cinema - that is, its technologically based copying of realit - is also the basis for film aesthetics. Film art's dependence on a rather technically complex apparatus has both stimulated and thwarted its development. At the very beginning of film history (and again in recent decades, e.g. Czesław Miłosz), traditionalists have denied cinema the status of art. On the other hand, members of historical and neo-avant-garde, as well as revolutionary forces have advocated for cinema's technological basis. In order to understand so-called realist traditions in film theory, we must abandon ontologically "naive realism" and accept a philosophy of ontological difference. Idiosyncratic theory based on personal experience of an aesthetic object may provide the missing common language between theory and practice, between the technical and aesthetic, between nomothetic and idiosyncratic approaches in humanities, social and natural sciences.
Keywords: avantgarde; avant-garde; creative process; film; film aesthetics; film theory; filmska estetika; mediality; medialnost; technology; tehnologija; ustvarjalna praksa